Analysis of Administrative Ethics and Leadership Styles in Improving Employee Performance at the Population and Civil Registration Service Palangka Raya City - Ari Sandy; Muhamad Rizqy Azima; Intan Kumalasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study examines the influence of administrative ethics and leadership style on employee performance at the Population and Civil Registration Office (Disdukcapil) of Palangka Raya City, highlighting their strategic role in strengthening public service governance. Using a quantitative explanatory survey design, data were collected from 80 employees through standardized Likert-scale questionnaires that had been tested for validity and reliability. The results reveal that administrative ethics has a dominant and statistically significant effect on employee performance, demonstrating that integrity, accountability, and transparency are critical determinants of service quality. Leadership style also exhibits a significant positive influence, particularly when leaders demonstrate transformational and ethical behavior that fosters motivation, communication, and organizational commitment. Furthermore, the combined effects of ethics and leadership generate a synergistic impact that enhances employee discipline, collaborative work culture, and operational efficiency. The regression model explains 65.9% of the variance in employee performance, indicating a strong predictive capacity. These findings underscore the necessity of reinforcing ethical governance and leadership capacity as a foundation for improving public service performance, especially within service institutions handling sensitive population data.